The PRIMARA study: a prospective, descriptive, observational study to review cinacalcet use in patients with primary hyperparathyroidism in clinical practice - Schwarz, P; Body, J J; Cáp, J; Hofbauer, L C; Farouk, M; Gessl, A; Kuhn, J M; Marcocci, C; Mattin, C; Muñoz Torres, M; Payer, J; Van De Ven, A; et al. (European journal of endocrinology, 2014)
OBJECTIVE: Medical management of primary hyperparathyroidism (PHPT) is important in patients for whom surgery is inappropriate. We aimed to describe clinical profiles of adults with PHPT receiving cinacalcet. DESIGN: A descriptive, prospective, observational study in hospital and specialist care centres. METHODS: For patients with PHPT, aged 23-92 years, starting cinacalcet treatment for the first time, information was collected on dosing pattern, biochemistry and adverse drug reactions (ADRs). Initial cinacalcet dosage and subsequent dose changes were at the investigator's discretion. RESULTS: Of 303 evaluable patients with PHPT, 134 (44%) had symptoms at diagnosis (mostly bone pain (58) or renal stones (50)). Mean albumin-corrected serum calcium (ACSC) at baseline was 11.4 mg/dl (2.9 mmol/l). The reasons for prescribing cinacalcet included: surgery deemed inappropriate (35%), patient declined surgery (28%) and surgery failed or contraindicated (22%). Mean cinacalcet dose was 43.9 mg/day (s.d., 15.8) at treatment start and 51.3 mg/day (31.8) at month 12; 219 (72%) patients completed 12 months treatment. The main reason for cinacalcet discontinuation was parathyroidectomy (40; 13%). At 3, 6 and 12 months from the start of treatment, 63, 69 and 71% of patients, respectively, had an ACSC of ≤10.3 mg/dl vs 9.9% at baseline. Reductions from baseline in ACSC of ≥1 mg/dl were seen in 56, 63 and 60% of patients respectively. ADRs were reported in 81 patients (27%), most commonly nausea. A total of 7.6% of patients discontinued cinacalcet due to ADRs. CONCLUSIONS: Reductions in calcium levels of ≥1 mg/dl was observed in 60% of patients 12 months after initiation of cinacalcet, without notable safety concerns.
Keywords: cinakalcet; dospělí; senioři nad 80 let; retrospektivní studie; Humans; lidé středního věku; Middle Aged; Aged, 80 and over; Europe; Young Adult; lékařská praxe - způsoby provádění; mladý dospělý; Naphthalenes; primární hyperparatyreóza; mužské pohlaví; Hyperparathyroidism, Primary; Adult; Cinacalcet; Evropa; ženské pohlaví; Dose-Response Relationship, Drug; vztah mezi dávkou a účinkem léčiva; lidé; Practice Patterns, Physicians'; Aged; naftaleny; senioři; Male; Retrospective Studies; Female